2018
DOI: 10.1038/s41467-018-04600-2
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1-mediated regulation of melanoma invasion

Abstract: Melanoma cells use different migratory strategies to exit the primary tumor mass and invade surrounding and subsequently distant tissues. We reported previously that ADAR1 expression is downregulated in metastatic melanoma, thereby facilitating proliferation. Here we show that ADAR1 silencing enhances melanoma cell invasiveness and ITGB3 expression. The enhanced invasion is reversed when ITGB3 is blocked with antibodies. Re-expression of wild-type or catalytically inactive ADAR1 establishes this mechanism as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 67 publications
(107 reference statements)
2
31
0
Order By: Relevance
“…In fact, the previous reports have revealed that PAX6 is correlated with angiogenesis, wherein it regulates the differentiation of endothelial cells and is associated with the expression of VEGF [26][27][28]. Our in vitro and in vivo assays suggest that PAX6 is essential for the process of angiogenesis of HUVECs by regulating the process of EMT, which agrees with the previously described consequence of overexpressing PAX6 for the pathogenesis of human cancers [29,30]. In an attempt to rescue the EGFL6-driven abnormal angiogenesis, we found that PAX6 depletion impaired the vascular malformation (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, the previous reports have revealed that PAX6 is correlated with angiogenesis, wherein it regulates the differentiation of endothelial cells and is associated with the expression of VEGF [26][27][28]. Our in vitro and in vivo assays suggest that PAX6 is essential for the process of angiogenesis of HUVECs by regulating the process of EMT, which agrees with the previously described consequence of overexpressing PAX6 for the pathogenesis of human cancers [29,30]. In an attempt to rescue the EGFL6-driven abnormal angiogenesis, we found that PAX6 depletion impaired the vascular malformation (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…6f). To date, although there has been no direct evidence to demonstrate that EGFL6 is correlated with PAX6, a study has shown that PAX6 regulates ITGB3 expression as a transcription factor [30]. Moreover, the members of the integrin family are Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Different possible mechanisms mediated by ADAR1 have also been revealed to play a role in carcinogenesis. In some of the studies, ADAR1 were found to regulate specific targets at the transcriptional- and post-transcriptional level and thereby inhibit cancer progression [31,64]. Tumor cells, particularly melanoma cells, has been demonstrated in these studies to downregulate ADAR1 expression in order to survive and migrate.…”
Section: The Role Of Adar1 In Modulating Specific Editing Substratmentioning
confidence: 99%
“…These editing events have been shown to play a role in self versus non-self RNA recognition in the innate immune response, and thus dysregulation of ADAR1 leads to immune-related diseases such as Aicardi-Goutieres syndrome (AGS) (Blango and Bass, 2016; Liddicoat et al, 2015; Mannion et al, 2014; Pestal et al, 2015; Rice et al, 2012). ADAR1 levels also correlate with tumor aggressiveness, as increases in ADAR1 editing suppress the innate immune response in tumors; accordingly, ADAR1 ablation helps with cancer therapy (Bhate et al, 2019; Gannon et al, 2018; Ishizuka et al, 2019; Liu et al, 2019; Nemlich et al, 2018). While the majority of ADAR1-regulated editing sites are found in repeat regions, ADAR2 is primarily responsible for editing adenosines found in non-repeat regions, particularly in the brain (Tan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%